Case Study in Ethics of Research: The Bucharest Early Intervention Project - Zeanah, Charles H. (2012)
The Bucharest Early Intervention Project is the first ever randomized controlled trial of foster care as an alternative to institutional care for young abandoned children. This paper examines ethical issues in the conceptualization and implementation of the study, which involved American investigators conducting research in another country, as well as vulnerable participants. We organize discussion of ethical questions about the study around several key issues. These include the nature and location of the vulnerable study population, the social value of conducting the study, risks and benefits of participating in the study to participants, and the post-trial obligations of the investigators. In discussing how these questions were addressed as the study was designed and after it was initiated, we describe our attempts to wed sound scientific practices with meaningful ethical protections for participants.